Essays on foreign direct investment and corruption: review and empirical study - Onody, Vanessa da Silva Mariotto (Universidade Federal de São Carlos, 2024)
Foreign Direct Investment (FDI) is a crucial development tool for many emerging regions. A specific issue explored in the international business literature is the relationship between corruption and FDI, examining whether corruption repels foreign investments (acting as "sand") or attracts more foreign investments (acting as "grease"). Several authors in the international literature have analyzed factors influencing the outcomes of this relationship, but few have investigated the role of corruption in FDI at the regional level, especially in emerging countries in Latin America, including Brazil. This thesis examines the relationship between corruption and regional concentration of FDI. To do so, two chapters (2 and 3) have been developed in the form of articles. The first is theoretical and serves to contextualize the research themes through a systematic literature review method, highlighting the trend of corruption as "sand" or "grease" in the analyzed studies. The next article, on the other hand, is applied, utilizing statistical analyses. To characterize this study, a new dataset with regional-level information on FDI is used to investigate whether foreign companies can tolerate some level of corruption in exchange for specific location-based advantages, thus challenging the binary view of the "sand" or "grease" hypothesis. As the main results, Chapter 2 revealed that research on macroeconomic factors is the most robust determinant in articles on the subject. These factors are understood to include institutional quality, governance, political and financial institutional risk, and business environments. Corruption is demonstrated in many studies as an indicator to be considered among other researched factors, observing the scarcity of research exclusively on the topic. After an extensive literature analysis, the main trend of the "sand or grease" hypothesis in emerging countries is concluded to lean towards "sand." With the third chapter, it was possible to empirically examine the sensitivity of multinational companies (MNCs) to corruption in the Latin American economy at the level of individual sectors. It was observed that corruption functions as a "lubricant" for both FDI and at the level of individual sectors. Finally, by using a non-linear approach, it was detailed that corruption functions as a lubricant for FDI only in regions with intermediate (medium-low) levels of corruption. This thesis provides a general contribution to national and international literature on the issue of the relationship between regional attractiveness of FDI and corruption in emerging countries in Latin America.
Essays on foreign direct investment and corruption: review and empirical study
Keywords: Corrupção; Investimento Estrangeiro Direto (IED); Brasil; São Paulo; Corruption; Foreign Direct Investment (FDI); Brazil; Sao Paulo; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA